Properties of the solution of some multipoint problems for integro-differential equation of Barbashin type - Nurmuhammet Gurbanmammedov; Parahat Gurbanmammedov; Ogulhan Haydarova (E-Journal of Analysis and Applied Mathematics)
The nonlocal boundary value problems for the nonlinear integro-differential Barbashin equation with a partial derivative of the second order is studied. The solution of the problem is understood in the classical sense. The problem reduces to the equivalent Volterra integral equation with partial integrals. The conditions for the existence and uniqueness of the solution of this equation are obtained.